(3QSGdI aj HjGf GdChbGa GdefRdIs - (3eLghds
(3ChdgG (B:s
(3aj HjGf GdChbGa GdefRdI NeSI YTQ ehVYG GdChd aj ShQI GdHbQI (B: (3hdG Nha Ydjge hdG ge jMRfhfs
(3BNQgG (B:s
(3Cdgce GdJcGKQ , GdSGOS YTQ hgh RGFO Yf gPg GdLedI hgh aj GdMTQ Jba Ydi daX GdMTQ Ke JHJOF eG XffJe Gf jNQLhGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs